Neutrino Oscillation Analysis of 217 Live Days of Daya Bay and 500 Live Days of RENO - Mario A. Acero; Alexis A. Aguilar-Arevalo; Dairo J. Polo-Toledo (Advances in High Energy Physics)
We present a neutrino oscillation analysis of two particular data sets from the Daya Bay and RENO reactor neutrino experiments aiming to study the increase in precision in the oscillation parameters sin22θ13 and the effective mass splitting Δmee2 gained by combining two relatively simple to reproduce analyses available in the literature. For Daya Bay, the data from 217 days between December 2011 and July 2012 were used. For RENO, we used the data from 500 live days between August 2011 and January 2012. We reproduce reasonably well the results of the individual analyses, both rate-only and spectral, defining a suitable χ2 statistic for each case. Finally, we performed a combined spectral analysis and extract tighter constraints on the parameters, with an improved precision between 30 and 40% with respect to the individual analyses considered.